Pengaruh Brand Positioning Dan Preferensi Merek Terhadap Niat Pembelian Produk Iphone Di Kota Sumenep - Rahman, Fathor; Kurdi, M; Liyanto, Liyanto (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2024)
The objective of this study is to analyse the influence of brand positioning and brand preference on the decision to purchase the iPhone in the city of Sumenep. One of the key players in the technology industry, particularly in the smartphone sector, is Apple. Renowned as one of the largest smartphone manufacturers globally, Apple is dedicated to enhancing customer satisfaction, particularly with its flagship product, the iPhone. The city of Sumenep was selected as the research context to examine consumer behaviour in the context of iPhone purchasing within a distinctive and competitive market environment. The research methodology employed was quantitative, with a descriptive statistical approach. The collected data were analysed using descriptive statistical techniques and regression analysis in order to identify the relationship between brand positioning and consumer preferences with regard to purchasing decisions. The findings of the study indicate that brand positioning has a significant influence on consumer purchasing decisions in the city of Sumenep. Factors such as product differentiation, brand image and associated brand values play an important role in influencing consumer purchasing decisions. Consumer preferences exert a positive influence on purchasing decisions. Consumers with a strong brand preference are more likely to have a positive intention to purchase an iPhone. This study offers valuable insights into the interplay between brand positioning and brand preference in the context of iPhone product purchases in Sumenep. The implications of this research include the importance of maintaining a robust brand positioning and developing marketing strategies that focus on enhancing brand preference to achieve optimal purchase intentions.